The Development of Entrepreneurial Intention Model Using Theory of Planned Behavior and Entrepreneurial Event - Wahono, Johannes Widjaja; Rumangkit, Stefanus (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2024)
Purpose – The aim of this research is to analyze the entrepreneurial intention model based on the theory of planned behavior and entrepreneurial events.Methodology – This research uses a quantitative research design with a positivism direction. The data source used is primary data, with data collection techniques namely questionnaires. the respondents of this study are 100 respondents of active students on the faculty of economics and business in Indonesia. The data analysis method used to test the hypothesis in this study is SEM (Structural Equation Modeling) with the help of SmartPLS software Findings – Based on the results of the research conducted, it can be concluded that Attitude has a positive effect on entrepreneurial intention, Subjective norm has a positive effect on entrepreneurial intention, Perceived Behavioral Control has a positive effect on entrepreneurial intention, propensity to act has a positive effect on entrepreneurial intention, and Entreprenurial intention has a positive effect on entrepreneurial goals.Originality/Novelty – The novelty of this research lies in combining the factors that form entrepreneurial intention from two theories, namely the theory of planned behavior and entrepreneurial events.Implications – To increase students' entrepreneurial desire or entreprenurial Intention, it is recommended to 1) Lecturers as course supervisors must be able to motivate students to create a new business that has sustainability. In addition, lecturers must also do business, in order to be able to tell how the business processes carried out can run continuously, 2) When lectures are running, peer groups of lecturers can invite one of the speakers both on a local and national scale to motivate, share knowledge, and foster entrepreneurial desires in students, and 3) Business incubators owned by institutions must monitor after students create businesses, so that the business contiguity can run.